(untitled) (Economics and region, 2020)
The article provides a set of recommendations for improving macroprudential regulation procedures, which can be grouped into blocks: overcoming systemic imbalances in the structure of banks’ assets and liabilities, dedollarization and overcoming currency imbalances, monitoring and minimizing sectoral imbalances, development of modern corporate governance systems and strengthening corporate governance functions of banking regulators, strategic solutions to the problem of state-owned banks. Proposals for improving the regulation of banks in the context of overcoming the effects of systemic risk implemented during crisis periods have been formulated. The ways of strengthening the macroprudential policy strategy in terms of both preventive and anti-crisis tools in order to ensure financial stability and increase the level of transparency in the banking market have been identified.